PENGARUH EFEKTIVTAS SISTEM INFORMASI AKUNTANSI, KESESUAIAN TUGAS DAN KEAHLIAN PEMAKAI TERHADAP KINERJA KARYAWAN DI PT. NASMOCO ABADI MOTOR - Widianti, Chrisputri; Ts, Kartika Hendra; Wijayanti, Anita (Prosiding Seminar Nasional: Manajemen, Akuntansi, dan Perbankan; Vol 1 No 1 (2018): Prosiding Seminar Nasional dan Call for Papers Manajemen, Akuntansi, dan Perbankan 2018, 2018)
The purpose of this study is to know and analyze the effect of accounting information system effectiveness, suitability, and expertise of the user on employee performance. The population of this study is all employees of PT Nasmoco Abadi Motor using accounting information system. The sample method used in this study is saturated sampling with the number of respondents obtained as many as 57 employees. Based on the results of multiple linear regression test assisted with SPSS 19.0 program, the first hypothesis shows that accounting information system has no effect on employee performance. While the second hypothesis that kesesuai positive tasks on employee performance, and the third hypothesis that has no effect on employee performance.